A Smart Theranostic Prodrug System Activated by Reactive Oxygen Species for Regional Chemotherapy of Metastatic Cancer. Issue 12 (3rd February 2022) - Liu, Lingyan; Liu, Feiyang; Liu, Dongya; Yuan, Wei; Zhang, Mengfan; Wei, Peng; Yi, Tao
Abstract: Metastatic cancer is difficult to cure because of its uncontrollable nature and side effects during treatment. We constructed a reactive oxygen species (ROS)‐activated smart theranostic prodrug system based on an ROS active site linked with both a targeting group and an anticancer drug for efficient regional chemotherapy of metastatic cancers. The optimized prodrug (Bio‐(8)‐MB‐CPT ) with biotin as the targeting group displayed high sensitivity towards ROS and selectively targeting ability towards cervical cancer cells, showing highly efficient drug release (up to 92 %) in vitro. Bio‐(8)‐MB‐CPT thus exerted strong toxicity towards cervical cancer cells, but unlike the parent drug (camptothecin), showed no toxicity towards normal cells. Moreover, the prodrug displayed significantly enhanced antitumor efficacy in vivo and eradicated the tumor with no obvious side effects (inhibition of the tumor reached up to 99.9 %). Abstract : A reactive oxygen species (ROS)‐activated smart theranostic prodrug system for efficient regional chemotherapy of metastatic cancers has been developed. The prodrug can selectively target cancer cells and be activated by highly expressed ROS, rapidly releasing drug with high efficiency. It shows significantly enhanced antitumor efficacy towards metastatic cancers (up to 99.9 %) with no obvious side effects.